Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)
fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Do nurses use discourse markers differently when using their second language as opposed to their first while interviewing patients? - Yeji, Han; Segalowitz, Norman; Khalil, Laura; Kehayia, Eva; Turner, Carolyn; Gatbonton, Elisabeth (The Canadian Modern Language Review, 2020)
Les auteurs se demandent si l’utilisation de marqueurs discursifs change, dans les interactions des infirmières avec les patients, en fonction de l’usage qu’elles font de leur langue maternelle (L1) ou de leur langue seconde (L2). Les marqueurs sont analysés à titre de marqueurs de maintien du tour de parole, indiquant la « prise en compte » et de marqueurs de transition dans le discours, indiquant un changement de sujet ou de locuteur dans la conversation. Ces deux catégories de marqueurs diffèrent sur le plan du degré de gestion du discours et du contrôle interactionnel. Seize infirmières mènent auprès d’un patient de L1 anglaise et d’un patient de L1 française un entretien visant l’évaluation de la douleur, entretien dans lequel les infirmières utilisent leur propre L1 dans un cas et leur propre L2, moins bien maîtrisée, dans l’autre. Les résultats de l’étude ne permettent pas de confirmer la première hypothèse, selon laquelle les infirmières devraient normalement utiliser les marqueurs discursifs plus fréquemment en L1 qu’en L2. Ils confirment toutefois la seconde hypothèse, selon laquelle les infirmières devraient utiliser les marqueurs de changement de sujet moins fréquemment en L2 qu’en L1, comparativement à leur usage (de base) des marqueurs de maintien du tour de parole. Les constatations des auteurs, en particulier l’attestation de la seconde hypothèse, pourraient avoir des répercussions sur le développement de la formation en L2 des professionnels de la santé.